2022
DOI: 10.1155/2022/9132477
|View full text |Cite|
|
Sign up to set email alerts
|

A Data-Driven Medical Decision Framework for Associating Adverse Drug Events with Drug-Drug Interaction Mechanisms

Abstract: Adverse drug events (ADEs) occur when multiple drugs interact within an individual, thus causing effects that were not initially predicted. Such toxic interactions lead to morbidity and mortality. Contemporary research surrounding ADEs has tended to focus on the detection of potential ADEs without great concern for elucidating the associations of drug-drug interaction (DDI) mechanisms that can predict potential adverse drug reactions (ADRs). Such associations are of great practical importance for everyday phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Several algorithms and strategies have been proposed by healthcare practitioners and researchers alike in attempts to address this perplexing subject. Our group previously developed a DDI prediction algorithm incorporating ten potential mechanisms [ 14 , 18 ]; other algorithms have been developed to predict DDIs and stratify risk based on available DDI resources [ 19 21 ]. A persistent challenge in all of these endeavors is the lack of proper validation data for the developed algorithms [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several algorithms and strategies have been proposed by healthcare practitioners and researchers alike in attempts to address this perplexing subject. Our group previously developed a DDI prediction algorithm incorporating ten potential mechanisms [ 14 , 18 ]; other algorithms have been developed to predict DDIs and stratify risk based on available DDI resources [ 19 21 ]. A persistent challenge in all of these endeavors is the lack of proper validation data for the developed algorithms [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These major symptoms may often be accompanied by fatigue from nasal discomfort, itching sensation around the eyes, swelling of the nasal mucosal membranes, postnasal dripping, and cough [ 1 ]. On the far current record, approximately 15–20% of the population around the globe is affected by AR, with a dominating ratio in western countries [ 2 , 3 ]. The treatment of the condition potentially focuses on alleviating the symptoms rather than addressing the root cause of the issue.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods for predicting DDIs constitute an area of considerable research interest, leading to the development of diverse methods and published resources. These methods have employed a variety of algorithms and utilized many features such as biological effect interactions [ 9 ], protein similarities [ 10 ], clinical and genomic factors [ 11 ], and drug-target [ 12 ] and drug-protein [ 13 ], as well as drug information on web [ 14 , 15 ], text-based data [ 14 ], protein interaction networks [ 16 ], mechanisms of toxicity [ 17 ], and enrichment analysis [ 18 ]. Among the diverse computational methods that have been used in DDI research, rule-based systems have shown especially promising results [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%